Anticipatory postural adjustments during cutting manoeuvres in football and their consequences for knee injury risk - Mornieux, G.; Gehring, D.; Fürst, P.; Gollhofer, A. (Journal of Sports Sciences, 2014)
Anticipatory postural adjustments (APAs), i.e. preparatory positioning of the head, the trunk and the foot, are essential to initiate cutting manoeuvres during football games. The aim of the present study was to determine how APA strategies during cutting manoeuvres are influenced by a reduction of the time available to prepare the movement.